2001
DOI: 10.1634/stemcells.19-2-134
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Adhesion Molecules on CD34 + Cells in Peripheral Blood of Non‐Hodgkin's Lymphoma Patients Mobilized with Different Growth Factors

Abstract: The mean percentage of CD34 + cells expressing VLA-4 in the BM and PB was relatively high (73.4% ± 12% and 65.4% ± 6.6%, respectively) and dropped considerably in the PBSC collections to 43.5% ± 7.1% with a similar pattern observed for patients in arms A, B, and C. However, when the patients were regrouped as "good mobilizers" and "poor mobilizers," a higher percentage of CD34 + cells expressing VLA-4 was observed in the PBSC of the pooled "good mobilizers" (50.5% ± 9% versus 36.3% ± 6.4%; p = 0.01). We conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 54 publications
3
14
0
Order By: Relevance
“…In our study, we found decreased levels of a4 and b1 integrin chains expressed on mobilized PB CD34 1 cells compared to BM cells, as previously reported (11,21,(23)(24)(25), together with decreased stroma adhesion capacity to BM stroma. This emphasizes the crucial role of VLA-4 in maintaining HPC within the BM microenvironment, as directly demonstrated by others (3)(4)(5).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we found decreased levels of a4 and b1 integrin chains expressed on mobilized PB CD34 1 cells compared to BM cells, as previously reported (11,21,(23)(24)(25), together with decreased stroma adhesion capacity to BM stroma. This emphasizes the crucial role of VLA-4 in maintaining HPC within the BM microenvironment, as directly demonstrated by others (3)(4)(5).…”
Section: Discussionsupporting
confidence: 90%
“…In recent studies, we also observed a decrease in the co-expression of VLA-4 and L-selectin on CD34 1 cells in the apheresis collections of NHL patients mobilized with cyclophosphamide plus G-CSF, GM-CSF, and GM-CSF followed by G-CSF, compared to CD34 1 cells in the steady-state bone marrow and peripheral blood (58,59). Furthermore, the decreases in the expression of VLA-4 and L-selectin on CD34 1 cells was observed in the apheresis collections of all patients, regardless of the growth factor used for mobilization.…”
Section: Factors Involved In the Release Of Pbscs Following G-csf Or mentioning
confidence: 64%
“…I T IS WIDELY ESTABLISHED that mobilization of peripheral blood stem cells (PBSCs) with hematopoietic growth factors such as granulocyte-colony-stimulating factor (G-CSF) or granulocyte macrophage (GM-CSF) involves down regulation of adhesion molecules such as VLA4, VLA5, CD44, and L-selectin (1)(2)(3)(4)(5)(6). Stromal derived factor-1 (SDF-1) is a chemokine and plays an important role in chemotaxis of many blood cells and in survival and proliferation of hematopoietic stem cells through activation of its specific receptor CXCR4.…”
Section: Introductionmentioning
confidence: 99%